Impact assessment of mixed land-use planning in Ethiopia: The case of Addis Ababa - Girmachew Tariku Jinoll; Liku Workalemahu; Dagnachew Adugna (Heliyon)
Urbanisation presents complex challenges that necessitate sustainable solutions for equitable resource distribution, environmental protection and economic growth. Mixed land-use planning (MLUP) offers a promising approach by integrating residential, commercial and recreational spaces, thereby enhancing urban resilience and inclusivity. However, its comprehensive impact on Addis Ababa remains underexplored, highlighting a notable research gap. This study aims to address this gap by examining the socio-economic, physical and environmental effects of MLUP across key Addis Ababa zones using a mixed-methods approach. Involving 384 households, 40 urban planning specialists and 14 key informants, including higher officials and diverse local community members from the Kir-kos and Bole sub-cities, the research used various sampling methods and data collected from 2002 to 2017 through surveys, interviews and observations. The analysis assesses MLUP's role in promoting economic growth, social cohesion, efficient land use and environmental sustainability. Findings reveal considerable variations in MLUP's impact on transportation and access to amenities, underscoring the need for context-specific planning. Insights from planners and community members highlight the benefits and challenges of MLUP and provide recommendations for improved urban planning practices that support sustainable urban environments.